2007
DOI: 10.1002/ppap.200600200
|View full text |Cite
|
Sign up to set email alerts
|

Helium Ion Irradiation of Polymer Films Deposited from TMS‐Ar Plasmas

Abstract: Polymer films synthesized from plasmas of a tetramethylsilane ‐ Ar mixture were modified by irradiation with 170 keV He ions at fluences ranging from 1 × 1014 to 1 × 1016 cm−2. As revealed by infrared spectroscopy, the ion beam produced intense bond rearrangements, such as the depletion of bonding groups (CH and SiH), and induced the formation of new ones, such as OH and SiO. From the nanoindentation measurements, a remarkable increase in the surface hardness of the films was observed as the ion fluence wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
3
0
3
Order By: Relevance
“…25-28 F. Z. Cui et al 25 studied the changes in protein secondary structure by low energy nitrogen ion beam irradiation due to the scission of H-bonds and charge exchange. Polymer lms synthesized from plasmas of a tetra methylsilane-Ar mixture using helium ion beam irradiation showed loss of hydrogen was reported by R. V. Gelamo et al 26 E. C. Rangel et al 27 investigate the effect of argon ion irradiation on polymer lm where signicant loss of hydrogen besides the formation of unsaturated bonds, and cross-links with decrease in electrical resistivity was found. Also the loss of hydrocarbon and the associated release of hydrogen is one of the consequences of the ion irradiation of polymer and polymer-like structures studied by D. L. Baptista et al 28 Here, such a mechanism is hypothesized for the L-MMT colloidal thin lm that the enhancement in sensitivity of the irradiated electrode could be due to the breakage of hydrogen bond induced by the as deposited L-MMT/ITO electrode.…”
Section: Methodsmentioning
confidence: 86%
“…25-28 F. Z. Cui et al 25 studied the changes in protein secondary structure by low energy nitrogen ion beam irradiation due to the scission of H-bonds and charge exchange. Polymer lms synthesized from plasmas of a tetra methylsilane-Ar mixture using helium ion beam irradiation showed loss of hydrogen was reported by R. V. Gelamo et al 26 E. C. Rangel et al 27 investigate the effect of argon ion irradiation on polymer lm where signicant loss of hydrogen besides the formation of unsaturated bonds, and cross-links with decrease in electrical resistivity was found. Also the loss of hydrocarbon and the associated release of hydrogen is one of the consequences of the ion irradiation of polymer and polymer-like structures studied by D. L. Baptista et al 28 Here, such a mechanism is hypothesized for the L-MMT colloidal thin lm that the enhancement in sensitivity of the irradiated electrode could be due to the breakage of hydrogen bond induced by the as deposited L-MMT/ITO electrode.…”
Section: Methodsmentioning
confidence: 86%
“…The mechanical properties of pp‐TVS films (10 W) with an elastic modulus and hardness of 11.7 and 0.82 GPa, respectively, may be increased by post‐deposition UV irradiation up to 14.1 and 1.02 GPa, respectively, after UV exposition for 1000 min . However, the plasma polymer films deposited at 35 W by PECVD from a mixture of tetramethylsilane and argon gas with a hardness of 1.2 GPa were hardened up to 12.7 GPa using helium ion irradiation (He + , 2.2 MeV) depending on ion fluence (1 × 10 14 −1 × 10 16 cm −2 ) …”
Section: Mechanical Properties Of Plasma Polymer Filmsmentioning
confidence: 89%
“…They observed the depletion of C-H and Si -H and formation of O-H and Si-O with increasing hardness. They concluded that the polymer structure transformed into a silicon oxycarbide network by irradiation [18]. Park et al conducted a dual-ion beam irradiation (including He ions, energy: 70 keV, fluence: 3 × 10 16 to 1 × 10 17 ions/cm 2 ) of a polymer blend to modify the optical properties of the coatings and improve the adhesion between the polymer surface and coating.…”
Section: Introductionmentioning
confidence: 99%